Visibility and Accessibility of Hand Hygiene Stations and Fatigue Among Nurses Working in Long-Term Care (LTC) During the COVID-19 Pandemic. (April 2023) - Cai, Hui; Garcia, Amy; Polivka, Barbara; Spreckelmeyer, Kent; Yang, Frances M.
Objectives: Evaluate the relationship between nurses' perception of the long-term care (LTC) environment, specifically having visible and accessible hand hygiene stations (HHS), and nurses' fatigue during the COVID-19 pandemic. Background: LTC nurses experience not only heavy workloads and fatigue but also a high risk of infection during the COVID-19 pandemic. Few studies have evaluated the relationship between safety measures such as having visible and accessible HHS and nurses' fatigue. Methods: The cross-sectional COVID-19 Impact on Nurses Study (COINS) was an online survey distributed to members of the American Association of Post-Acute Care Nursing through the REDCap survey platform, between June 1, 2020, and January 31, 2021. Logistic regression modeling was conducted to identify the relationship between nurses' perception of having visible and accessible HHS and fatigue among LTC nurses. Results: The majority of LTC nurse respondents (78.35%) reported having moderate to very severe fatigue. Nurses who reported not having enough visible and accessible HHS in their work environment have statistically significantly higher odds (odds ratio [ OR ] = 0.37, 95% confidence interval [CI] [0.20, 0.70], p = .002) of reporting experiencing moderate to very severe fatigue compared to nurses who perceived there was adequate HHS. The logistic regression is significant while controlling for sociodemographic differences, guilt for family and patients, support from work, and confidence in the future of LTC. Conclusions: This study reveals the LTC environment that incorporates better considerations of more visible and accessible HHS might mitigate nurses' fatigue during the pandemic. A conceptual framework has been proposed for future studies.